Na2Se-C composite sodium supplement as well as preparation method and application thereof
By preparing Na2Se@C composite sodium supplementation agent, the problem of excessive consumption of active sodium during the circulation of sodium ion batteries was solved, and the effect of improving the battery energy density and cycle life was achieved.
Patent Information
- Application Number
- CN202510062052.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-15
AI Technical Summary
During the circulation process, sodium ion batteries consume too much active sodium due to negative electrode SEI generation and side reaction, resulting in low efficiency of Coulomb, capacity loss and energy density reduction. The existing sodium supplementation method is costly and has safety hazards.
Na2Se@C composite sodium supplement agent is used, which is prepared by drying, purifying, mixing and annealing treatment of Na2Se and carbon covering its surface. The mass percentage of Na2Se is 80% to 98% by weight and the particle size is 1 to 10μm.
Na2Se@C composite sodium supplementation agent can effectively supplement sodium ion loss, improve the positive electrode conductivity, enhance air stability, reduce the "dead mass" of the battery, and improve the energy density and cycle life of the sodium ion battery.
Smart Images

Figure CN119864422A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery electrode material and a preparation method and application thereof, in particular to a Na2Se@C composite sodium supplement and a preparation method and application thereof. Background Art
[0002] Sodium resources are abundant and widely distributed, so sodium-ion batteries are expected to become one of the most popular next-generation energy storage systems. Sodium and lithium are both alkali metal elements, and their working mechanism is similar to that of lithium-ion batteries. During the charging process, an oxidation reaction occurs at the positive electrode, and sodium ions are released from the positive electrode, passing through the diaphragm and migrating to the negative electrode. Electrons flow to the negative electrode through an external circuit, and electrical energy is converted into chemical energy. The discharge process is the opposite, and chemical energy is converted into electrical energy. The development of sodium-ion batteries can alleviate the problem of lithium resources and expand the market for new secondary batteries.
[0003] Sodium-ion batteries have significant cost advantages. However, the radius of sodium ions is larger than that of lithium ions, resulting in a lower sodium content in the positive electrode. In addition, the formation of negative electrode SEI and side reactions during the cycle will consume a large amount of active sodium, resulting in lower coulombic efficiency, which in turn leads to irreversible capacity loss and reduced energy density of sodium-ion batteries. Therefore, research on sodium supplementation has attracted the interest of many scientific researchers. According to the different sodium supplementation methods, it can be divided into negative electrode sodium supplementation, diaphragm and positive electrode sodium supplementation. Negative electrode sodium supplementation generally involves rolling sodium powder or sodium foil directly onto the surface of the electrode under a certain pressure, and the additional sodium source added in advance can be used to compensate for the sodium consumed during the battery cycle. However, this method has a cumbersome and difficult manufacturing process, which leads to high costs, and once sodium metal is excessively added, it will cause the growth of sodium dendrites, bringing safety issues. Positive electrode sodium supplementation mostly uses a sodium supplement agent mixed with a positive electrode material to make a slurry. During the first charging process, the sodium supplement agent is oxidized to release additional sodium ions to compensate for the active sodium consumed by the negative electrode.
[0004] The positive electrode sodium supplements NaN3, Na2O, Na3C6H5O7, Na2C6O6 and Na2CO3 currently used in sodium-ion batteries will produce various gases such as O2, N2 and CO2 during the sodium supplement process, which will cause the battery to bulge and leave residues inside the battery, bringing useless "dead mass" and reducing the battery's energy density. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a Na2Se@C composite sodium supplementer that can effectively supplement sodium loss, has no gas generation and inert substance residue, can improve the positive electrode conductivity and has strong air stability; another purpose of the present invention is to provide a simple, safe, efficient and low-cost preparation method of the Na2Se@C composite sodium supplementer; the present invention also provides an application of the Na2Se@C composite sodium supplementer in the positive electrode material of a sodium ion battery.
[0006] Technical solution: The Na2Se@C composite sodium supplement described in the present invention comprises Na2Se and carbon coated on the surface of Na2Se, wherein the mass percentage of Na2Se is 80wt% to 98wt%.
[0007] Furthermore, the particle size of the Na2Se@C composite sodium supplement is 1 to 10 μm.
[0008] The preparation method of a Na2Se@C composite sodium supplement agent of the present invention comprises the following steps:
[0009] Step 1: For the chemical formula Na2Se x O y The selenium source is dried and purified by carbon pretreatment, wherein x=1, 2, y=0, 2, 3, 4;
[0010] Step 2: The pretreated selenium source and carbon are fully mixed in a mass ratio of 1:0.1 to 0.5, and then ground and sieved to obtain a mixture; the carbon in this ratio can fully reduce sodium selenite to generate Na2Se@C, and the sodium supplementing agent particles obtained by grinding and sieving have a moderate particle size and optimal performance;
[0011] Step 3: anneal the mixture in an inert gas atmosphere, heat it to 500-900°C, keep it warm, and cool it to obtain a Na2Se@C composite sodium supplement. If the reaction temperature is above 500°C, carbon cannot fully reduce sodium selenite, and the product will be rich in impurity sodium diselenide; if the reaction temperature is higher than 900°C, the product will decompose, increase energy consumption and make the product particle size uneven. The inert gas atmosphere avoids oxidative decomposition of carbon and reaction products.
[0012] Na2Se is a promising sodium supplement. However, as an active metal compound, Na2Se is easily reacted with water, oxygen, etc. in the air. When selenium powder reacts with sodium metal in the presence of liquid ammonia, it is not only necessary to isolate the air during the reaction, but the use of liquid ammonia also brings safety problems, making its synthesis difficult. The method for synthesizing the Na2Se@C composite sodium supplement is simple, safe and efficient, and the compound with carbon can enhance the air stability of Na2Se.
[0013] Furthermore, the selenium source in step one is one or more of Na2SeO3·5H2O, Na2SeO4, Na2SeO4·10H2O, Na2SeO2, and Na2Se2.
[0014] Furthermore, the grinding in step 2 is planetary ball milling, the material-ball ratio is 1:1-10, the ball milling speed is set at 300-800rpm, and the ball milling time is 6-12h. A ball mill, a resonance mixer, a spiral mixer, etc. can be used. The uniform mixing allows the sodium selenite to fully contact with the carbon, preparing for the next step of annealing. The sieving process can ensure the uniformity of the particles to achieve the best effect.
[0015] Furthermore, the heating rate of step three is 1-5°C / min.
[0016] Furthermore, the heat preservation time of step 3 is 4 to 12 hours. If the reaction time is less than 4 hours, sodium selenite cannot completely generate sodium selenide; if the reaction time is more than 12 hours, the target product Na2Se@C particles will agglomerate and the particle size will be large and uneven, which will increase the reaction energy consumption.
[0017] Furthermore, the carbon is one or more of Ketjen black, acetylene black, conductive carbon black, activated carbon, graphite, carbon nanotubes, and graphene.
[0018] The invention discloses an application of a Na2Se@C composite sodium supplement in a positive electrode material for a sodium ion battery.
[0019] Furthermore, the mass ratio of Na2Se@C composite sodium supplement to positive electrode active material in sodium ion battery is 1:4 to 99. This ratio ensures the best sodium supplement effect, and Na2Se@C can effectively supplement the lost active sodium to improve energy density.
[0020] Principle of the invention: Na2Se can provide a high theoretical specific capacity of 675mAh / g, and no additional gas or useless residue will be produced during the sodium supplementation process. The conductivity of solid selenium after sodium removal is about 10 -5 S / cm, further improving the conductivity of the composite positive electrode. Na2Se has a high theoretical specific capacity, but it is easy to react with water and oxygen in the air. Composite with carbon can increase its air stability and conductivity. The Na2Se@C composite sodium supplement is prepared by carbon thermal reduction. Sodium selenite and carbon materials are fully mixed, ground and sieved in proportion. Under high temperature and inert gas protection conditions, the reducing agent C reduces the O in sodium selenite to generate CO2 gas, and the product Na2Se and carbon coated on the surface of Na2Se are obtained, namely Na2Se@C sodium supplement. Na2Se@C is added to the positive electrode material of sodium ion battery as a sodium supplement. During charging, Na2Se@C reacts to release sodium ions to supplement the active sodium consumed by the formation of negative electrode SEI. The polyselenide shuttled to the negative electrode can promote sodium ion transmission, improve battery conductivity, inhibit dendrite growth, and is conducive to the improvement of cycle life.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0022] 1. Na2Se and C in the synthesized Na2Se@C composite sodium supplement have good synergistic effects. C improves the air stability of Na2Se and the energy density of the battery, which makes it possible for the large-scale application of Na2Se.
[0023] 2. The synthesis method of Na2Se@C composite sodium supplement is simple, safe and efficient, which changes the existing complex synthesis process. No difficult-to-degrade waste is generated during the synthesis process. It is green and environmentally friendly and can be mass-produced;
[0024] 3. Na2Se@C composite sodium supplementer has excellent sodium supplementation effect in the application of sodium ion batteries, which can effectively improve the energy density and cycle life of sodium ion batteries. It can solve the gas production problem and inert substance residue problem of existing sodium supplementers in the process of sodium supplementation, and promote the commercialization process of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the X-ray diffraction pattern of the Na2Se@C composite sodium supplement of Example 1 of the present invention;
[0026] Figure 2 This is a scanning electron microscope image of the Na2Se@C composite sodium supplement of Example 1 of the present invention;
[0027] Figure 3 This is the first cycle charge and discharge curve of the Na2Se@C composite sodium supplement agent of Example 1 of the present invention;
[0028] Figure 4 This is a comparison chart of the cycle performance of sodium ion batteries to which the Na2Se@C composite sodium supplement of Example 1 of the present invention is added. DETAILED DESCRIPTION
[0029] In the following examples, the materials and reagents used are all commercially available unless otherwise specified. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0030] Example 1
[0031] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0032] Sodium selenite and carbon were dried and purified for pretreatment. 1g sodium selenite and 0.1g acetylene black were weighed and placed in a planetary ball mill with a material-ball ratio of 1:5. After adding ball milling beads, the mixture was milled continuously at a speed of 500rpm for 10 hours to obtain a uniformly mixed mixture, and the mixture was sieved through a 1500-mesh sieve. The mixture was then transferred to a tubular furnace, and the furnace temperature was raised to 800°C at a heating rate of 5°C / min in an argon atmosphere. After keeping the temperature for 10 hours, it was naturally cooled to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0033] Figure 1 This is the X-ray diffraction result of the prepared Na2Se@C composite sodium supplement. The diffraction peaks are consistent with those on the standard card, confirming the synthesis of Na2Se.
[0034] Figure 2 This is a scanning electron microscope image.
[0035] Example 2
[0036] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0037] Na2SeO4 and carbon were dried and purified for pretreatment, 1g Na2SeO4 and 0.5g Ketjen black were weighed, placed in a planetary ball mill, with a material-ball ratio of 1:1, and ball milled at 300rpm for 6h after adding ball milling beads to obtain a uniformly mixed mixture, and the mixture was sieved through a 1500 mesh. The mixture was then transferred to a tubular furnace, and the furnace temperature was raised to 500℃ at a heating rate of 1℃ / min in an argon atmosphere, and after being kept warm for 4h, it was naturally cooled to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0038] Example 3
[0039] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0040] Na2SeO2 and carbon were dried and purified for pretreatment. 1g Na2SeO2 and 0.2g graphite were weighed and placed in a planetary ball mill with a material-ball ratio of 1:3. After adding ball milling beads, the mixture was milled at a speed of 400rpm for 7h to obtain a uniformly mixed mixture. The mixture was sieved through a 1500-mesh sieve. The mixture was then transferred to a tubular furnace, and the furnace temperature was raised to 600℃ at a heating rate of 2℃ / min in an argon atmosphere. After keeping the temperature for 6h, it was naturally cooled to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0041] Example 4
[0042] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0043] Na2Se2 and carbon were dried and purified for pretreatment, 1g Na2Se2 and 0.3g conductive carbon black were weighed and placed in a planetary ball mill with a material-to-ball ratio of 1:7. After adding ball milling beads, the mixture was ball milled at a speed of 600rpm for 9h to obtain a uniformly mixed mixture, and the mixture was sieved through a 1500-mesh sieve. The mixture was then transferred to a tubular furnace, and the furnace temperature was raised to 700℃ at a heating rate of 3℃ / min in an argon atmosphere. After being kept warm for 8h, it was naturally cooled to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0044] Example 5
[0045] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0046] Sodium selenite and carbon were dried and purified for pretreatment, 1g sodium selenite and 0.4g carbon nanotubes were weighed, placed in a planetary ball mill, with a material-ball ratio of 1:10, and ball milled at 800rpm for 12h after adding ball milling beads to obtain a uniformly mixed mixture, and the mixture was sieved through a 1500-mesh sieve. The mixture was then transferred to a tube furnace, and the furnace temperature was raised to 900℃ at a heating rate of 4℃ / min in an argon atmosphere, and after being kept warm for 12h, it was naturally cooled to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0047] Example 6
[0048] The remaining steps of this embodiment are the same as those of embodiment 1, with the only difference being that sodium selenite is replaced with Na2SeO4, Na2SeO2, and Na2Se2 in sequence to obtain the target product, Na2Se@C composite sodium supplement.
[0049] Comparative Example 1
[0050] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0051] Unlike Example 1, Comparative Example 1 was not subjected to ball milling. 1 g of sodium selenite and 0.1 g of acetylene black were weighed and mixed thoroughly. The mixture was transferred to a tube furnace, and the furnace temperature was raised to 800° C. at a heating rate of 5° C. / min in an argon atmosphere. After being kept warm for 10 h, the mixture was naturally cooled to room temperature to obtain the target product, Na2Se@C composite sodium supplement.
[0052] Comparative Example 2
[0053] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0054] Different from Example 1, 1 g of sodium selenite and 0.6 g of acetylene black were weighed and placed in a planetary ball mill with a material-to-ball ratio of 1:5. After adding ball mill beads, the mixture was continuously ball milled at a speed of 500 rpm for 10 hours to obtain a uniformly mixed mixture, and the mixture was sieved through a 1500 mesh screen. The mixture was then transferred to a tubular furnace, and the furnace temperature was raised to 800°C at a heating rate of 5°C / min in an argon atmosphere. After being kept warm for 10 hours, it was naturally cooled to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0055] Comparative Example 3
[0056] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0057] Different from Example 1, the annealing temperature is 400°C and the holding time is 3h. Weigh 1g of sodium selenite and 0.1g of acetylene black, place them in a planetary ball mill, the material-ball ratio is 1:5, add ball milling beads, and mill them continuously at a speed of 500rpm for 10h to obtain a uniformly mixed mixture, and pass the mixture through a 1500 mesh sieve. Then transfer the mixture to a tubular furnace, raise the furnace temperature to 400°C at a heating rate of 5°C / min in an argon atmosphere, keep warm for 3h, and naturally cool to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0058] Comparative Example 4
[0059] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0060] Different from Example 1, the annealing temperature is 1000°C and the holding time is 13h. Weigh 1g of sodium selenite and 0.1g of acetylene black, place in a planetary ball mill, the material-ball ratio is 1:5, add ball milling beads, and mill continuously at a speed of 500rpm for 10h to obtain a uniformly mixed mixture, and pass the mixture through a 1500 mesh sieve. Then transfer the mixture to a tubular furnace, raise the furnace temperature to 1000°C at a heating rate of 5°C / min in an argon atmosphere, keep warm for 13h, and naturally cool to room temperature to obtain the target product Na2Se@C composite sodium supplement.
[0061] Comparative Example 5
[0062] The preparation method of Na2Se@C composite sodium supplement comprises the following steps:
[0063] Different from Example 1, the target product is Na2Se. 1g of sodium selenite and 0.08g of acetylene black are weighed and placed in a planetary ball mill with a material-to-ball ratio of 1:5. After adding ball milling beads, the mixture is continuously ball milled at a speed of 500rpm for 10 hours to obtain a uniformly mixed mixture, and the mixture is sieved through a 1500 mesh screen. The mixture is then transferred to a tubular furnace, and the furnace temperature is raised to 800°C at a heating rate of 5°C / min in an argon atmosphere. After keeping the temperature for 10 hours, it is naturally cooled to room temperature to obtain the target product Na2Se sodium supplement.
[0064] The Na2Se@C composite sodium supplement obtained in the above embodiments and comparative examples was used as an electrode material to prepare a battery pole piece and assemble it into a button battery (CR2032) for testing, including the following steps:
[0065] The Na2Se@C composite sodium supplement obtained in the above-mentioned embodiments and comparative examples was mixed with a binder of polyvinylidene fluoride (PVDF) and a conductive agent of acetylene black in a mass ratio of 80:10:10, and then 1-methyl-2-pyrrolidone (NMP) was added and stirred evenly to form a slurry, which was evenly coated on the surface of the aluminum foil. After drying at 85°C for 12 hours, it was pressed by a roller press and cut into electrode sheets. The prepared electrode sheets were assembled into button batteries (CR2032) for testing. Metallic sodium was used as the counter electrode, 1.0M NaClO4 (EC:PC=3:7) was used as the electrolyte, and a glass fiber diaphragm was used as the diaphragm. After the assembled battery was placed for 24 hours, a charge and discharge test was carried out in a voltage range of 1.2-4V at a room temperature of 25°C. The electrochemical performance test results of the Na2Se@C composite sodium supplement obtained in the embodiments and comparative examples are shown in Table 1. Figure 3 As shown, in the voltage range of 1.2-4V, the charge capacity of Na2Se@C prepared in Example 1 as an electrode material is 455mAh / g, and the discharge capacity is only 66.2mAh / g.
[0066] Table 1 Electrochemical performance test results
[0067]
[0068]
[0069] Table 2 Electrochemical performance test results of Example 6
[0070] Selenium source <![CDATA[Charge specific capacity / mAh·g -1 > <![CDATA[Discharge specific capacity / mAh·g -1 > <![CDATA[Na2SeO4]]> 445.3 56.3 <![CDATA[Na2SeO2]]> 438.4 67.3 <![CDATA[Na2Se2]]> 423.6 52.7
[0071] According to Table 1, Table 2 and Figure 3It is concluded that the Na2Se@C composite sodium supplement of the present invention has excellent electrochemical performance as an electrode material, among which the Na2Se@C composite sodium supplement prepared by reacting sodium selenite with carbon in Example 1 has the best performance as an electrode material. In the voltage range of 1.2-4V, the battery charging capacity of the Na2Se@C composite sodium supplement as an electrode material is 455mAh / g, and the discharge capacity is only 66.2mAh / g. By comparing Example 1 with Comparative Example 1, it can be seen that the ball milling treatment significantly reduces the particle size, helps to accelerate the migration of ions and electrons during the electrochemical reaction, and significantly improves its kinetic process.
[0072] The Na2Se@C composite sodium supplement obtained in Example 1 was used as the experimental group, and the Na2S@C composite sodium supplement was used as the control group to verify the improvement of the battery charge and discharge performance. The charge and discharge capacity of the prepared battery is shown in Table 2. The battery preparation includes the following steps:
[0073] Application Examples
[0074] The Na2Se@C obtained in Example 1 was uniformly mixed with sodium vanadium phosphate in a mass ratio of 5:95 as an electrode active material, and then mixed with a binder polyvinylidene fluoride (PVDF) and a conductive agent acetylene black in a ratio of 80:10:10, and 1-methyl-2-pyrrolidone (NMP) was added and stirred to form a slurry, which was uniformly coated on the surface of aluminum foil, and then dried at 85°C for 12 hours to obtain an electrode sheet. The electrode sheet was pressed by a roller press and then dried at 90°C for 8 hours, and cut into a sodium ion battery positive electrode sheet.
[0075] The prepared electrode sheets were assembled into button batteries (CR2032) for testing. Hard carbon was used as the negative electrode, 1.0M NaClO4 (EC:PC=3:7) was used as the electrolyte, and a glass fiber separator was used as the diaphragm. After the assembled battery was placed for 24 hours, a constant current charge and discharge cycle test was performed at a rate of 0.5C at room temperature of 25°C, with a voltage range of 1.2 to 4V. The test results are shown in Figure 4 As shown in the figure, after adding the Na2Se@C composite sodium supplement, the first cycle discharge capacity of the sodium ion battery increased from 78.45 mAh / g to 103.5 mAh / g. At a rate of 0.5C, after 200 cycles, the discharge capacity remained at 90.1 mAh / g.
[0076] Application comparison
[0077] Weigh 1g of sodium sulfite and 0.1g of acetylene black, place them in a planetary ball mill with a material-ball ratio of 1:5, add ball milling beads and continue ball milling at a speed of 500rpm for 10 hours to obtain a uniformly mixed mixture, pass the mixture through a 1500-mesh sieve, transfer it to a tubular furnace, and in an argon atmosphere, raise the furnace temperature to 800℃ at a heating rate of 5℃ / min. After keeping warm for 10 hours, naturally cool to room temperature to obtain a Na2S@C sodium supplement.
[0078] The Na2S@C obtained in the control group was uniformly mixed with sodium vanadium phosphate at a mass ratio of 5:95 as the electrode active material, and then mixed with the binder polyvinylidene fluoride (PVDF) and the conductive agent acetylene black at a ratio of 80:10:10, and 1-methyl-2-pyrrolidone (NMP) was added and stirred to form a slurry, which was evenly coated on the surface of aluminum foil and then dried at 85°C for 12 hours to obtain an electrode sheet. The electrode sheet was pressed by a roller press and then dried at 90°C for 8 hours, and cut into sodium ion battery positive electrode sheets.
[0079] The prepared electrode sheets were assembled into button batteries (CR2032) for testing. Hard carbon was used as the negative electrode, 1.0M NaClO4 (EC:PC=3:7) was used as the electrolyte, and a glass fiber separator was used as the diaphragm. After the assembled battery was placed for 24 hours, a constant current charge and discharge cycle test was performed at a rate of 0.5C at room temperature of 25°C, with a voltage range of 1.2 to 4V.
[0080] Table 3 Battery charge and discharge capacity
[0081] serial number <![CDATA[Initial charge specific capacity / mAh·g -1 > <![CDATA[Initial discharge specific capacity / mAh·g -1 > Application Examples 121.7 103.5 Application comparison 106.0 98.4
[0082] From Table 3 and Figure 4 It can be seen that the Na2Se@C composite sodium supplement can release excess active sodium ions in the full battery and exert an excellent sodium supplement effect in practical applications.
Claims
1. A Na2Se@C composite sodium supplement, characterized in that: The invention comprises Na2Se and carbon coated on the surface of Na2Se, wherein the mass percentage of Na2Se is 80wt% to 98wt%.
2. The Na2Se@C composite sodium supplement according to claim 1, characterized in that: The particle size of the Na2Se@C composite sodium supplement is 1-10 μm.
3. A method for preparing a Na2Se@C composite sodium supplement, characterized in that: The following steps are involved: Step 1: For the chemical formula Na2Se x O y The selenium source is dried and purified by carbon pretreatment, wherein x=1, 2, y=0, 2, 3, 4; Step 2, the pretreated selenium source and carbon are fully mixed in a mass ratio of 1:0.1-0.5, and then ground and sieved to obtain a mixture; Step three, annealing the mixture in an inert gas atmosphere, heating it to 500-900° C. and then keeping the temperature, and cooling it to obtain a Na2Se@C composite sodium supplement.
4. The method for preparing the Na2Se@C composite sodium supplement according to claim 3, characterized in that: The selenium source in step 1 is one or more of Na2SeO3·5H2O, Na2SeO4, Na2SeO4·10H2O, Na2SeO2, and Na2Se2.
5. The method for preparing the Na2Se@C composite sodium supplement according to claim 3, characterized in that: The grinding in step 2 is planetary ball milling, the material-ball ratio is 1:1-10, the speed of the ball mill is set at 300-800 rpm, and the ball milling time is 6-12 hours.
6. The method for preparing the Na2Se@C composite sodium supplement according to claim 3, characterized in that: The heating rate of step three is 1-5°C / min.
7. The method for preparing the Na2Se@C composite sodium supplement according to claim 3, characterized in that: The insulation time of step three is 4 to 12 hours.
8. The method for preparing the Na2Se@C composite sodium supplement according to claim 3, characterized in that: The carbon is one or more of Ketjen black, acetylene black, conductive carbon black, activated carbon, graphite, carbon nanotubes, and graphene.
9. Use of the Na2Se@C composite sodium supplement according to any one of claims 1 to 2 in a positive electrode material for a sodium ion battery.
10. The use of the Na2Se@C composite sodium supplement according to claim 9 in a positive electrode material for a sodium ion battery, characterized in that: The mass ratio of the Na2Se@C composite sodium supplement to the positive electrode material in the sodium ion battery positive electrode material is 1:4-99.
Citation Information
Patent Citations
Application of Na2S as positive sodium supplement additive of pre-sodium-modified positive pole piece
CN116314798A
Sodium carbonate / carbon composite positive electrode sodium supplement additive, preparation method thereof and application of sodium carbonate / carbon composite positive electrode sodium supplement additive in negative-electrode-free sodium metal battery
CN117199360A
Sodium-sulfur battery and preparation method and application thereof
CN117199497A
Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and secondary battery
CN117766763A
Sodium supplementing material and preparation method thereof, positive pole piece and sodium ion battery
CN118867247A